Productivity effects of business process outsourcing: a firm-level investigation based on panel data - Jörg Ohnemus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper analyses the impact of business process outsourcing (BPO) on firm productivity based on a comprehensive German firm-level panel data set covering manufacturing and service industries. The growing importance of service inputs into the production process is undisputed. Firms increasingly buy all or at least parts of selected services they need from external service providers. This is especially true for services which rely to a great extent on new information and communication technologies. Outsourcing firms can concentrate on their core competencies. Additionally, they benefit from the expertise of the external service provider. Finally, external vendors are able to provide services at lower price because of scale effects. By estimating a production function, I show that BPO has a positive and significant impact on firm-level productivity. The results are robust across different estimation techniques.
Keywords: C23; D24; L24; L60; L80; 330; Business Process Outsourcing (BPO); Productivity; Panel Data; Olley-Pakes; System-GMM; Outsourcing; Produktivität; Unternehmensentwicklung; Schätzung; Deutschland